Allium schoenoprasum L.: a review of phytochemistry, pharmacology and future directions. Issue 18 (17th September 2018) - Singh, Varinder; Chauhan, Gargi; Krishan, Pawan; Shri, Richa
Abstract: Allium schoenoprasum L. (family Amaryllidaceae), commonly known as chives has great culinary value besides being used as ethnomedicine. This review emphasises on phytochemistry and pharmacological activities of A. schoenoprasum, and discusses the future opportunities for systematic investigations. Scientific evaluation of chives validates its traditional claims and demonstrates diverse pharmacological potential including an anti-inflammatory, anticancer, antioxidant, anthelmintic and antihypertensive. Though phytochemical studies revealed the presence of sulphur and phenolic compounds, flavonoids, saponin and steroidal glycosides yet methodical research to identify bioactive compounds is required. This review confirms the medicinal importance of A. schoenoprasum and could stimulate future research on its unexplored aspects, especially identification of bioactive compounds and related mechanisms and safety, which might develop it as a drug. Abstract :